2021
DOI: 10.1093/neuros/nyab297
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Age and Severity on Dementia After Traumatic Brain Injury: A Comparison Study

Abstract: BACKGROUND Growing evidence associates traumatic brain injury (TBI) with increased risk of dementia, but few studies have evaluated associations in patients younger than 55 yr using non-TBI orthopedic trauma (NTOT) patients as controls to investigate the influence of age and TBI severity, and to identify predictors of dementia after trauma. OBJECTIVE To investigate the relationship between TBI and dementia in an institutional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“… 14 As was shown previously, the risk of dementia is higher in older individuals with any TBI severity. 14 , 28 This suggests a subacute-chronic disease state rather than simply higher diagnostic scrutiny or an immediate complication of acute brain injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 14 As was shown previously, the risk of dementia is higher in older individuals with any TBI severity. 14 , 28 This suggests a subacute-chronic disease state rather than simply higher diagnostic scrutiny or an immediate complication of acute brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…There was a higher risk of psychotic disorders in the middle-aged and older subgroups, replicating the results of prior studies . As was shown previously, the risk of dementia is higher in older individuals with any TBI severity . This suggests a subacute-chronic disease state rather than simply higher diagnostic scrutiny or an immediate complication of acute brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Brain injuries trigger various neurological complications, including epilepsy, depression, and dementia ( Burke et al, 2021 ; Stopa et al, 2021 ; Wang et al, 2021 ). Our observations revealed that adolescent traumatic brain injury results in spatial memory impairment and anxiety/depression-like behavior in middle-aged mice, which is consistent with the previous study ( Mao et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…13 A single episode of TBI is considered sufficient for the adverse effect, 14 and chronic pathologies following single versus multiple cases of TBI show many similarities. 14 TBI is a risk factor for Alzheimer's disease (AD) and other dementias, [15][16][17][18] although dissenting opinions based on recent biologic studies question whether TBI causes AD-consistent pathologic changes and suggest that TBI, although associated with neurodegenerative processes, may not be associated with AD specifically. [19][20][21] Independent of the exact biologic mechanism, the prevention of the consequences of dementia, of which AD is the most common pathologic cause, 22 poses the current challenge for the US health system.…”
Section: E385mentioning
confidence: 99%